Meroanencephaly in an English Pointer Neonate - Cerqueira da Silva, Luisa Mariano; Piúma Gonçalves, Helena; dos Santos, Thaís Cozza; de Castro, Clarissa Caetano; Fernandes, Cristina Gevehr; Grecco, Fabiane Borelli; Varela Junior, Antonio Sergio; Corcini, Carine Dahl (Acta Scientiae Veterinariae, 2020)
Background: Malformations are structural or functional abnormalities in the organs and structures present at birth. These conditions are rarely described in the newborns of dogs and can lead to their death. Meroanencephaly is a defect of the neural tube closure malformation. This study aims to characterize the clinical-pathological aspects of neonatal meroanencephaly since brain malformations are rare in newborn dogs. Case: A two-day-old English Pointer canine was sent for a necropsy. The newborn belonged to a litter of eight puppies, and only this one had macroscopic cranial alterations. Another puppy that died as a consequence of being trampled by the bitch was also necropsied. The newborn was alive for 48 h until death and presented apathy, crying, sucking reflex and opisthotonus. Macroscopic examination of the baby revealed flattening of the skull, with a slit at the site of bone symphysis fusion, and a slit in the skin of the parietal region, covered by thin, translucent meningeal tissue. The heads of the two animals were examined by radiography to identify the features of anencephaly in one of the animals by visualizing skull bone flattening. Upon removing the skin and exposing the cranial cavity, an irregular reddish mass was revealed, that corresponded microscopically to area cerebrovasculosa, composed of neurons, rudimentary glial tissue, vascular neoformations, as well as hemorrhagic areas. Discussion: Meroanencephaly is a type of anencephaly, a congenital malformation originating from abnormal neurulation, which results from the absence of neural fold fusion during neural tube formation. Live-born anencephalics have some brainstem-driven functions such as spontaneous breathing and some reflex responses, for instance, suction. Several genetic or teratogenic factors, such as viruses, radiation, drugs administered during pregnancy and other pathologies transmitted from bitch to fetus, can lead to this defect. The reports on anatomopathological findings and the presence of area cerebrovasculosa are rare.